2013
DOI: 10.1126/scitranslmed.3006135
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII Is Essential for the Proasthmatic Effects of Oxidation

Abstract: Increased reactive oxygen species (ROS) contribute to asthma, but little is known about the molecular mechanisms connecting increased ROS with characteristic features of asthma. We show that enhanced oxidative activation of the Ca2+/calmodulin-dependent protein kinase (ox-CaMKII) in bronchial epithelium positively correlates with asthma severity and that epithelial ox-CaMKII increases in response to inhaled allergens in patients. We used mouse models of allergic airway disease induced by ovalbumin (OVA) or Asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 67 publications
(108 reference statements)
5
90
1
Order By: Relevance
“…Our group originally discovered that CaMKII is activated by ROS (ox-CaMKII) (9) and that ox-CaMKII is increased in airway epithelium from asthmatic patients after allergen exposure where it correlates with asthma severity (8). In subsequent studies, we found that mitochondrial-targeted antioxidant therapy protects against inflammation and fibrosis in OVA-challenged mice (10).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our group originally discovered that CaMKII is activated by ROS (ox-CaMKII) (9) and that ox-CaMKII is increased in airway epithelium from asthmatic patients after allergen exposure where it correlates with asthma severity (8). In subsequent studies, we found that mitochondrial-targeted antioxidant therapy protects against inflammation and fibrosis in OVA-challenged mice (10).…”
Section: Introductionmentioning
confidence: 90%
“…While numerous studies have provided evidence that asthma is a pleiotropic disease marked by increased airway ROS, the molecular mechanisms that connect ROS to asthma phenotypes are uncertain (4)(5)(6)(7). We recently made the unanticipated discovery that the multifunctional Ca 2+ /calmodulin-dependent protein kinase II (CaM-KII) in airway epithelium is a key regulator of the ROS-linked asthmatic phenotypes of inflammation, eosinophilic recruitment and infiltration, and airway hyperreactivity (AHR) in murine models of allergic asthma (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased OxiCaMKII levels were also detected in OVA challenged allergic asthma mice, compared with vehicle treatment, without any significant increase in total CaMKII levels. Moreover, the Oxi-CaMKII levels were higher in severe asthmatics compared with mild asthmatics and healthy individuals, suggesting that Oxi-CaMKII is not only an indicator of asthma but also a marker of disease severity (61 …”
Section: Oxidative-camkii (Oxi-camkii) Inhibitormentioning
confidence: 99%
“…Oxidative CaMKII was increased in airway epithelium biopsied from mildly asthmatic patients and OVA or aspergillus fumigatus challenged mouse models (61). A mouse model that evaluated airway epithelium with a specific deficiency in CaMKII expression showed clinical features that included inhibition of AHR airway epithelial proliferation and mucus secretion (62).…”
Section: Inflammatory Cellsmentioning
confidence: 99%